Assessing the impact of funding sources and financial literacy on SMME growth in Stadium area constituency Maseru, Lesotho - Dichaba, Madintletse Anna (Central University of Technology, 2022)
Small, Medium, and Micro Enterprises (SMMEs) are critical for both economic and social development in developing countries. The SMME sector contributes significantly to the Gross Domestic Product (GDP) through lowering unemployment, alleviating poverty, and encouraging entrepreneurship. The purpose of the study is to assess the impact of funding sources and financial literacy on SMMEs growth in Stadium Area Constituency Maseru Lesotho. Quantitative approach was used in this study and data collection was through close-ended questionnaires. Data is analysed and presented in the form of Structural Equation Modeling (SEM). The study addressed the questions such as how sources of funding and financial literacy impact SMMEs growth. The study revealed that, the correlation coefficient between internal financing and entrepreneurial skills is very weak (𝑟 = 0.15), though it is positively correlated with the significant value of (𝑃 < ,001) , and external financing has a significant positive correlation with entrepreneurial skills(𝑟 = 0.91), with the significant value of (𝑃 < ,001). It is therefore concluded that,if more resources can be put in external financing, that is, if SMMEs owners can get external funding either from commercial banks, or from any financial institutions to acquire entrepreneurial skills, this may lead to SMME growth and its sustainability which can impact positively to the country’s economy. It is recommended that, policymakers and decision makers should help entrepreneurs, by designing curriculum for entrepreneurial skills short courses, to equip SMMEs owners with skills and knowledge, on how to run their businesses effectively and efficiently, as the way for sustainability, viability and growth of their businesses.
Thesis (M.Phil: Management Sciences)--Central University of Technology
Keywords: Small Medium and Micro Enterprises (SMMEs); Source of funding; Financial literacy; Commercial banks; SMMEs growth